Homomeric assemblies of NMDAR1 splice variants are sensitive to ethanol. - Koltchine, V; Anantharam, V; Wilson, A; Bayley, H; Treistman, SN (1993)
Studies have shown that the neuronal NMDA receptor is a target for the actions of ethanol. Recently, a number of subunits of the NMDA receptor have been cloned and functionally expressed in various combinations. We have expressed four splice variants of the NMDAR1 subunit in Xenopus oocytes, and find that homomeric assemblies of this subunit, in the absence of other subunits, exhibit ethanol sensitivity comparable to that seen in neurons. In the presence of calcium, the reduction of total current was greatest in the NMDAR1-LL splice variant, and was significantly less in the NMDAR1-SS variant. The increased sensitivity of NMDAR1-LL may be attributed to a particularly sensitive slow current 'hump' which is more pronounced in NMDAR1-LL than in NMDAR1-SS. The reduction of NMDA-evoked current by ethanol was significantly different when calcium was replaced by barium in the external medium. In this case, the slow current hump was significantly reduced, current through NMDAR1-LL was less reduced by ethanol, and the percent reduction of NMDAR1-LL and NMDAR1-SS currents was similar. NMDA-evoked currents in heteromeric receptors formed by coinjection of the mouse epsilon-1 subunit with the NMDAR1 splice variants responded to ethanol similarly to homomeric assemblies.